New Amides and Phosphoramidates Containing Selenium: Studies on Their Cytotoxicity and Antioxidant Activities in Breast Cancer - Mikel Etxebeste-Mitxeltorena; Daniel Plano; Nora Astrain-Redín; Cristina Morán-Serradilla; Carlos Aydillo; Ignacio Encío; Esther Moreno; Socorro Espuelas; Carmen Sanmartín (MDPI AG, 2021)
Breast cancer is a multifactor disease, and many drug combination therapies are applied for its treatment. Selenium derivatives represent a promising potential anti-breast cancer treatment. This study reports the cytotoxic activity of forty-one amides and phosphoramidates containing selenium against five cancer cell lines (MCF-7, CCRF-CEM, HT-29, HTB-54 and PC-3) and two nonmalignant cell lines (184B5 and BEAS-2B). MCF-7 cells were the most sensitive and the selenoamides I.1f and I.2f and the selenium phosphoramidate II.2d, with GI50 values ranging from 0.08 to 0.93 µM, were chosen for further studies. Additionally, radical scavenging activity for all the compounds was determined using DPPH and ABTS colorimetric assays. Phosphoramidates turned out to be inactive as radical scavengers. No correlation was observed for the antioxidant activity and the cytotoxic effect, except for compounds I.1e and I.2f, which showed dual antioxidant and antitumor activity. The type of programmed cell death and cell cycle arrest were determined, and the results provided evidence that I.1f and I.2f induced cell death via autophagy, while the derivative II.2d provoked apoptosis. In addition, Western blot analysis corroborated these mechanisms with an increase in Beclin1 and LC3-IIB and reduced SQSTM1/p62 levels for I.1f and I.2f, as well as an increase in BAX, p21 and p53 accompanied by a decrease in BCL-2 levels for derivative II.2d.